P505 Factors influencing outcomes from surgery for Crohn's disease: A perspective from a district hospital. (16th January 2018) - Aspari, A R; Husain, N; Thomas, P
Abstract: Background: Crohn's disease has always posed a challenge to surgeons especially in the light of newer biological agents and immunosuppression. Although medical management of Crohn's disease has changed in the recent years, it is unclear whether surgical management during the various stages of the disease has an impact. We present our series with the aim of evaluating the effect of various factors on outcomes from surgical intervention for Crohn's disease. Methods: Consecutive patients undergoing surgical intervention for Crohns disease were recruited. Factors such as pre-operative medications including steroids, immunosuppressant and biologics, ASA grade, indications for surgery, emergency or elective surgery and laparoscopic or open surgery were analysed against outcomes from the surgery including complications [Clavien-Dindo classification], recurrence and remission period from surgery. Results: A majority of the patients that eventually required surgical intervention were in the age group of 20–30 years at the time of diagnosis. A time period of 10–15 years would have elapsed before they require their first surgical intervention in majority of patients. Few patients required their first surgical intervention within 5 years of diagnosis. In decreasing order of frequency, the indications for surgery were intestinal obstruction, internal fistulae, enterocutaneous fistula and adverse reaction to immunomodulators/biologics. Most of the patients were on three classes (aminosalicylates, steroids, immunomodulators or immunosuppressants) of medical management at the time surgical intervention is required. Moreover, the duration of being on medical treatment varied between 2 and 19 years before surgical intervention was done. The various surgeries that were carried out were right hemicolectomy, pan-proctocolectomy, segmental ileocolic resection and small-bowel resections. These were carried out laparoscopically where feasible with a low conversion rate. Of the complications encountered, very few were beyond Clavien-Dindo class II. The median remission time was 5 years. Recurrence within a 5-year period appeared to be related to margin positivity following surgery. Conclusions: Surgery remains an important component of the multi-modality treatment of IBD, required in 70–80% of patients with Crohn`s disease. The use of pre-operative steroids and immunosuppressants did not appear to increase our rate of complications. In our series, there was a 20–30% symptomatic recurrence rate in the first year after surgery, with a 10% increase in each subsequent year. These recurrence rates were influenced by the use of Infliximab and azathioprine along with steroids in the post-operative phase.